Anomalous Enhancement of Proton Conductivity for Water Molecular Clusters Stabilized in Interstitial Spaces of Porous Molecular Crystals. Issue 42 (3rd September 2014) - Tadokoro, Makoto; Ohhata, Yuki; Shimazaki, Yuriko; Ishimaru, Shin'ichi; Yamada, Teppei; Nagao, Yuki; Sugaya, Tomoaki; Isoda, Kyosuke; Suzuki, Yuta; Kitagawa, Hiroshi; Matsui, Hiroshi
Abstract In an investigation into the proton conductivity of crystallized water clusters confined within low‐dimensional nanoporous materials, we have found that water‐stable nanoporous crystals are formed by complementary hydrogen bonding between [CoIII(H2bim)3]3+ (H2bim: 2, 2′‐biimidazole) and TATC3− (1, 3, 5‐ tricarboxyl‐2, 4, 6‐triazinate); the O atoms in the COO− groups of TATC3− in the porous outer wall are strongly hydrogen bonded with H2O, forming two types of WMCs (water molecular clusters): a spirocyclic tetramer chain (SCTC) that forms infinite open 1D channels, and an isolated cyclic tetramer (ICT) present in the void space. The ICT is constructed from four H2O molecules as a novel C2‐type WMC, which are hydrogen bonded with four‐, three‐, and two‐coordination spheres, respectively. The largest structural fluctuation is observed at elevated temperatures from the two‐coordinated H2O molecules, which begin to rapidly and isotropically fluctuate on heating. This behavior can be rationalized by a simple model for the elucidation of pre‐melting phenomena, similar to those in ice surfaces as the temperature increases. Moreover, high proton conductivity of SCTCs (ca. 10−5 S cm−1 at 300 K with an activation energy of 0.30 eV) through a proton‐hole mechanism was observed for pellet samples using the alternating impedance method. The proton conductivity exhibits a slight enhancement of about 0.1×10−5 S cm−1 at 274 K due to a structural transition upon approaching this temperature that elongates the unit cell along the b‐axis. The proton‐transfer route can be predicted in WMCs, as O(4) of an H2O molecule at the center of an SCTC shows a motion that rotates the dipole in the b‐axis direction, but not the c‐axis; the thermal ellipsoids of O(4) based on anisotropic temperature factors obtained by X‐ray crystallography reflect a structural fluctuation along the b‐axis direction induced by [CoIII(H2bim)3]3+.